Genetic effects of XRCC4 and ligase IV genes on human glioma. Issue 14 (28th September 2016) - Jiao, Keping; Qin, Juan; Zhao, Yumei; Zhang, Honglian
Abstract : Ligase IV and XRCC4 genes, important molecules in the nonhomologous end-joining pathway for repairing DNA double-strand breaks, may play crucial roles in carcinogenesis. To detect their effects on the risk of human glioma, their gene expression differences between 110 human glioma tissues and 50 healthy brain tissues were determined using quantitative real-time PCR. Furthermore, two tagging single nucleotide polymorphisms (SNPs) in ligase IV and four SNPs in XRCC4 genes were genotyped in 317 glioma patients and 352 healthy controls. The association of glioma and ligase IV/XRCC4 was evaluated using methods for SNP, haplotype, and gene–gene interaction analysis. Compared with those in normal brain tissues, the relative gene expression levels of ligase IV and XRCC4 were significantly downregulated in glioma tissue ( P =0.0017 and 0.0006, respectively). Single SNP analysis indicated that only rs10131 in ligase IV remained significantly associated with glioma ( P =0.0036) after 10 000 permutation tests. Haplotype analysis showed that the haplotype profiles of ligase IV and XRCC4 were significantly different between glioma patients and healthy controls ( P =0.004 and 3.13E−6, respectively). Finally, the gene–gene interaction analysis suggested that the three-locus model (rs1805388, rs10131, and rs2075685) was the best model for ligase IV and XRCC4 to have interaction effects on the risk of glioma. In conclusion, both ligase IV and XRCC4 may act in concert to modulate the development of glioma. Abstract : Supplemental Digital Content is available in the text.